Solvability of a Coupled System of Fractional Differential Equations with Periodic Boundary Conditions at Resonance - Zhigang Hu; Wenbin Liu (Український математичний журнал, 2013)
By using the coincidence degree theory, we study the existence of solutions for a coupled system of fractional differential equations with periodic boundary conditions. A new result on the existence of solutions of the indicated fractional boundary-value problem is obtained.